Analisis Cloud Computing Untuk Penyimpanan Dokumen Terhadap Proses Pembelajaran Menggunakan Algoritma Regresi Linear Berganda (Studi Kasus : SMA Chandra Kusuma Jakarta Utara) - Sukirman Sukirman (Jurnal Ilmiah Informatika, 2022)
Obstacles in the learning process carried out by subject teachers and students of SMA Chandra Kusuma School, North Jakarta, because document storage is still low and internet access is still slow. Multiple linear regression algorithm to determine the relationship between cloud computing variables and the learning process on document storage variables. Simultaneously the F test results are 15.387 and the coefficient of determination is 36.30% so that there is a significant relationship between cloud computing and the learning process for document storage. Partially, cloud computing for document storage has a significant relationship because it has a t-value of 3.211 which is greater than t-table. And partially the learning process for document storage there is a significant relationship because it has a t-count value of 3.824 which is greater than t-table.